2021
DOI: 10.2174/1573403x16666200621160742
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin Modulates the Expression of mRNAs and miRNAs Related to Stemness in Endometrial Cancer

Abstract: Background: Salinomycin, an ionophore antibiotic, has a strong anti-cancer effect, inducing the apoptosis of cancer cells and cancer stem cells. Objective: The aim of the study was to assess the influence of salinomycin on the expression profile of genes related to stemness and miRNA regulating their expression in endometrial cancer cells. Methods: Endometrial cancer cells of cell line Ishikawa were exposed to salinomycin at concentrations in the range of 0.1- 100 µM, with the aim of determining its pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Most miRs have previously been reported to be deregulated in EC (Donkers et al, 2021). For instance, a reduced level of miR-374 and miR-374a in EC cell lines has been validated (Jayaraman et al, 2017;Talkowski et al, 2021). As for miR-374a-3p, it has been revealed that increased expression of miR-374a-3p contributes to restraining the biological activities of non-small-cell lung cancer cells (NSCLCs), (Yang et al, 2020), while the miR-374a-3p function in EC has remained largely unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Most miRs have previously been reported to be deregulated in EC (Donkers et al, 2021). For instance, a reduced level of miR-374 and miR-374a in EC cell lines has been validated (Jayaraman et al, 2017;Talkowski et al, 2021). As for miR-374a-3p, it has been revealed that increased expression of miR-374a-3p contributes to restraining the biological activities of non-small-cell lung cancer cells (NSCLCs), (Yang et al, 2020), while the miR-374a-3p function in EC has remained largely unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Conventional treatments such as radiotherapy, chemotherapy, and surgery are common cancer therapy methods, but they often lead to tumour recurrence. This recurrence is mainly because conventional therapies only target the bulk of the tumour, leaving cancer stem cells (CSCs) behind, and they are believed to be the driving force of tumour progression [ 5 , 6 , 7 , 8 ]. CSCs are a subset of a tumour [ 2 , 9 ] as they mimic stem cell features, including active proliferation and the ability to metastasise, self-renew, and differentiate.…”
Section: Introductionmentioning
confidence: 99%